Expeditive synthesis of trithiotriazine-cored glycoclusters and inhibition of Pseudomonas aeruginosa biofilm formation - Smadhi, Meriem; de Bentzmann, Sophie; Imberty, Anne; Gingras, Marc; Abderrahim, Raoudha; Goekjian, Peter G. (Beilstein Journal of Organic Chemistry, 2014)
Readily accessible, low-valency glycoclusters based on a triazine core bearing D-galactose and L-fucose epitopes are able to inhibit biofilm formation by Pseudomonas aeruginosa. These multivalent ligands are simple to synthesize, are highly soluble, and can be either homofunctional or heterofunctional. The galactose-decorated cluster shows good affinity for Pseudomonas aeruginosa lectin lecA. They are convenient biological probes for investigating the roles of lecA and lecB in biofilm formation.
Keywords: antibiotic; biofilm; glycocluster; lectin; multivalency effect; multivalent glycosystems